Validation of the Internal Structure of a German-Language Version of the Gender Role Conflict Scale – Short Form - Komlenac, Nikola; Siller, Heidi; Bliem, Harald R.; Hochleitner, Margarethe (Frontiers in Psychology, 2018)
The Gender Role Conflict Scale-Short Form (GRCS-SF) assesses a person’s masculine gender role conflict. Masculine gender role conflict results when a person experiences discomfort showing a certain behavior because it is in conflict with masculine norms. The aim of the study was to test the questionnaire’s psychometric properties in an Austrian sample of older men. Three alternative structural models of the GRCS-SF were tested with confirmatory factor analyses (CFA). The maximum likelihood method and the Bollen-Stine Bootstrap method were used to estimate the fit indices of the CFA. Convergent validity was tested by correlating the GRCS-SF with the Sexual Performance Belief Scale (SPBS). Participating in the study were 127 male in-patients of a university hospital. Men’s average age was 59.5 (SD = 14.6) years. The one-factor model did not fit the empirical data well. In contrast, both the four-factor structure model and the bifactor structure model were supported. Good internal consistencies indicated acceptable reliabilities of the questionnaire’s scales. As expected, moderate to large correlations with the SPBS were detected. These findings support the claim that the GRCS-SF is a reliable and valid tool for assessing men’s gender role conflict also in a sample of older men in Austria.